Mobile applications for natural parks: guidelines study for the development of a mobile device application - Melo, Luís Brasil de (2016)
Context aware mobile applications are being adopted as a premium solution to enhance and augment the user experience of visitors of natural parks and other public and open spaces. Under this assumption, this paper reports on a selection of existent mobile park applications featuring a set of tests that helped electing their key features. The performed evaluation also allowed setting up a proposal for design guidelines aiming the development of such a kind of applications.